Environmental impact study on a degassing and scaling of cistern trucks for fuel transportation plant. - Tupia, Elmer (2001)
The present Study of Environmental Impact (EIA) it is carried out by the Company Ecoplanet Group from the Peru CORP, to application of Servisya CORP, proprietor of a degassing plant and scaling of trucks cistern for transports of derived liquid fuels of the hydrocarbons, the environment of the location area undestood in the Country of Lima of the district of Villa El Salvador being.